Uptake of pH-Sensitive Gold Nanoparticles in Strong Polyelectrolyte Brushes - Kesal, Dikran (Polymers (Basel), 2016)
The impact of electrostatic attraction on the uptake of gold nanoparticles (AuNPs) into positively charged strong poly-[2-(Methacryloyloxy) ethyl] trimethylammonium chloride (PMETAC) polyelectrolyte brushes was investigated. In this work, PMETAC brushes were synthesized via surface-initiated atom transfer radical polymerization (Si-ATRP). PMETAC/AuNP composite materials were prepared by incubation of the polymer brush coated samples into 3-mercaptopropionic acid-capped AuNP (5 nm in diameter) suspension. The electrostatic interactions were tuned by changing the surface charge of the AuNPs through variations in pH value, while the charge of the PMETAC brush was not affected. Atomic-force microscopy (AFM), ellipsometry, UV/Vis spectroscopy, gravimetric analysis and transmission electron microscopy (TEM) were employed to study the loading and penetration into the polymer brush. The results show that the number density of attached AuNPs depends on the pH value and increases with increasing pH value. There is also strong evidence that the particle assembly is dependent on the pH value of the AuNP suspension. Incubation of PMETAC brushes in AuNP suspension at pH 4 led to the formation of a surface layer on top of the brush (2D assembly) due to sterical hindrance of the clustered AuNPs, while incubation in AuNP suspension at pH 8 led to deeper particle penetration into the brush (3D assembly). The straightforward control of particle uptake and assembly by tuning the charge density of the nanoparticle surface is a valuable tool for the development of materials for colorimetric sensor applications.